Novel Browning Agents, Mechanisms, and Therapeutic Potentials of Brown Adipose Tissue. (25th December 2016) - Wankhade, Umesh D.; Shen, Michael; Yadav, Hariom; Thakali, Keshari M.
Abstract : Nonshivering thermogenesis is the process of biological heat production in mammals and is primarily mediated by brown adipose tissue (BAT). Through ubiquitous expression of uncoupling protein 1 (Ucp1) on the mitochondrial inner membrane, BAT displays uncoupling of fuel combustion and ATP production in order to dissipate energy as heat. Because of its crucial role in regulating energy homeostasis, ongoing exploration of BAT has emphasized its therapeutic potential in addressing the global epidemics of obesity and diabetes. The recent appreciation that adult humans possess functional BAT strengthens this prospect. Furthermore, it has been identified that there are both classical brown adipocytes residing in dedicated BAT depots and "beige" adipocytes residing in white adipose tissue depots that can acquire BAT-like characteristics in response to environmental cues. This review aims to provide a brief overview of BAT research and summarize recent findings concerning the physiological, cellular, and developmental characteristics of brown adipocytes. In addition, some key genetic, molecular, and pharmacologic targets of BAT/Beige cells that have been reported to have therapeutic potential to combat obesity will be discussed.